THE VULNERABILITY ANALYSIS OF FLOOD AND FLOOD DISASTER MANAGEMENT IN CODE WATERSHED, YOGYAKARTA - - Nurhadi; Dyah Respati Suryo Sumunar; Nurul Khotimah (Jurnal Penelitian Saintek, 2016)
This study aims to determine: (1) the vulnerability of cold lava ﬂ ood disaster along the banks of the River Yogyakarta City Code, and (2) the direction of ﬂ ood disaster management cold lava along the banks of the River Code of Yogyakarta. Research carried out along the banks of the River Code that was in the city of Yogyakarta from May to October 2013. The study population is along the banks of the Code River in the area of the city of Yogyakarta. Samples were along the river bank area code affected and not affected by cold lava ﬂ ood. Data collected by the method of documentation, interviews, and ﬁ eld checks. The data analysis technique is quantitative analysis with tumpangsusun/ overlay parameters tiered ﬂ ood weighted using GIS. The results showed that: (1) The area on the banks of the River Code that have medium levels of vulnerability is ﬂ ooding the medium category and Gowongan Cokrodiningratan region, while the region with the vulnerability of ﬂ ood prone category is Sosromenduran region, Suryatmajan, Prawirodirjan, Keparakan, Brontokusuman, and Sorosutan, (2) Referral to the revitalization plan for ﬂ ood prevention Code River settlements to be more effective and safer from disasters, namely through the revitalization of the vertical and horizontal.